Analyzing the content of the two science books (the two chemistry units) for the intermediate stage according to environmental problems (Journal Of Educational and Psychological Researches, 2022)
The main goal of the current research is to know -Environmental problems included in the content of the two science books (chemistry units) for intermediate stageA list of environmental problems had been prepared  and  consisting of (8) main areas which are (air and atmosphere pollution, water pollution, soil pollution, energy, disturbance of biodiversity and environmental balance, waste management, food and medicinal pollution, investment of mineral wealth). Of which (60) sub-problems,  at that time the researcher analyzed the two science books (two chemistry units) for the intermediate stage of the academic year (2020-2021) in light of the list that was prepared, and the validity and consistency were assured, and the results showed, that The two science books (two chemistry units) for the first intermediate grade achieved (19) sub-problems with a percentage of (31.66%), and the two science books for the second intermediate grade,  achieved (15) sub-problems with a percentage of (25%))In the light of the results of the research, the researcher recommends including the content of the two science books     ( two units of  chemistry) for the intermediate stage, the main and sub-environmental problems that are not available as one of the modern trends in scientific education.  In the light of Environmental problems themselves.